Modelling of changes in the corneal endothelium after cataract surgery and penetrating keratoplasty. - Bates, A K (1992)
Long term changes in endothelial cell density were monitored in three groups of patients after surgery. One group underwent uncomplicated cataract surgery, one group complicated cataract surgery which eventually progressed to corneal decompensation, and one group penetrating keratoplasty. A mathematical model is presented which describes endothelial cell loss after surgery as an exponential decay process towards an asymptote with constant rate of cell loss over time. When fitted to the data from the three groups there is excellent agreement in each case. Discriminant analysis techniques were applied to model predictions to assess the likelihood of late corneal decompensation after surgery. From measurements of endothelial cell density before and after surgery we were able to correctly assign patients undergoing cataract surgery to decompensation or non-decompensation groups in 85.7% and 92.7% of cases respectively.